2019
DOI: 10.1103/physrevlett.122.146802
|View full text |Cite
|
Sign up to set email alerts
|

High-Magnetic-Field Tunneling Spectra of ABC -Stacked Trilayer Graphene on Graphite

Abstract: ABC-stacked trilayer graphene (TLG) are predicted to exhibit novel many-body phenomena due to the existence of almost dispersionless flat-band structures near the charge neutrality point (CNP). Here, using high magnetic field scanning tunneling microscopy, we present Landau Level (LL) spectroscopy measurements of high-quality ABC-stacked TLG. We observe an approximately linear magneticfield-scaling of the valley splitting and orbital splitting in the ABC-stacked TLG. Our experiment indicates that the valley sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 55 publications
(70 reference statements)
2
15
0
Order By: Relevance
“…Our measurements have been repeated on several samples showing ABCA domains, indicating the robustness of the gap values we measure. One question that arises is why ABCA graphene displays such a correlated gap, while ABC graphene has not displayed this phenomenon in previous spectroscopic measurements (28). To answer this question, we quantify the sharpness of the ABCA LDOS peak by extracting the half-width of the most prominent peak in the spectrum at each value of gate voltage.…”
Section: Resultsmentioning
confidence: 98%
“…Our measurements have been repeated on several samples showing ABCA domains, indicating the robustness of the gap values we measure. One question that arises is why ABCA graphene displays such a correlated gap, while ABC graphene has not displayed this phenomenon in previous spectroscopic measurements (28). To answer this question, we quantify the sharpness of the ABCA LDOS peak by extracting the half-width of the most prominent peak in the spectrum at each value of gate voltage.…”
Section: Resultsmentioning
confidence: 98%
“…The values of tight-binding parameters γ 0,...,4 and δ have been constrained in the literature from fits to experimental data [14,31] and ab initio simulations [10,[32][33][34]. However, due to the large number of parameters and limited data availability, there exist significant discrepancies between these estimates.…”
Section: Band Structure Modelmentioning
confidence: 99%
“…In graphene monolayer, the Coulomb energy is compatible with the measured valley splitting at  = 0. However, at present, the approximately linear B-scaling of the valley splitting in graphene is beyond the description of any existed theory 16,37 and more theoretical works are needed to fully understand this phenomenon. Moreover, our experiment demonstrated that the valley splitting depends sensitively on the filling factor: for example, the valley splitting decreases about 25% at  = -1 even though the magnetic field is higher ( Fig.…”
mentioning
confidence: 99%